Leptin Receptors in RIP-Cre25Mgn Neurons Mediate Anti-dyslipidemia Effects of Leptin in Insulin-Deficient Mice - Singha, Ashish; Palavicini, Juan Pablo; Pan, Meixia; Farmer, Scotlynn; Sandoval, Darleen; Han, Xianlin; Fujikawa, Teppei (Frontiers in Endocrinology, 2020)
Leptin is a potent endocrine hormone produced by adipose tissue and regulates a broad range of whole-body metabolism such as glucose and lipid metabolism, even without insulin. Central leptin signaling can lower hyperglycemia in insulin-deficient rodents via multiple mechanisms, including improvements of dyslipidemia. However, the specific neurons that regulate anti-dyslipidemia effects of leptin remain unidentified. Here we report that leptin receptors (LEPRs) in neurons expressing Cre recombinase driven by a short fragment of a promoter region of Ins2 gene (RIP-Cre25Mgn neurons) are required for central leptin signaling to reverse dyslipidemia, thereby hyperglycemia in insulin-deficient mice. Ablation of LEPRs in RIP-Cre25Mgn neurons completely blocks glucose-lowering effects of leptin in insulin-deficient mice. Further investigations reveal that insulin-deficient mice lacking LEPRs in RIP-Cre25Mgn neurons (RIP-Cre∆LEPR mice) exhibit greater lipid levels in blood and liver compared to wild-type controls, and that leptin injection into the brain does not suppress dyslipidemia in insulin-deficient RIP-Cre∆LEPR mice. Leptin administration into the brain combined with acipimox, which lowers blood lipids by suppressing triglyceride lipase activity, can restore normal glycemia in insulin-deficient RIP-Cre∆LEPR mice, suggesting that excess circulating lipids are a driving-force of hyperglycemia in these mice. Collectively, our data demonstrate that LEPRs in RIP-Cre25Mgn neurons significantly contribute to glucose-lowering effects of leptin in an insulin-independent manner by improving dyslipidemia.